The Concept of Criminal Justice For Drug Abuse: A Legal Approach - Dahlan, Dahlan; Ahmed, Zahoor; Saraya, Sitta (Jurnal Hukum, 2025)
The narcotics law is implemented on the basis of justice. However, its enforcement does not reflect a sense of justice because there is no classification of drug abusers. This study aims to analyze the criminal law policy on drug crimes and analyze the reconstruction of the law in the application of criminal sanctions for drug abusers for themselves based on the value of justice. This study used a normative legal method. The application of criminal sanctions for drug users in judicial practice is often inconsistent and does not reflect justice, especially due to differences in judges' interpretations and the absence of recognition of attempted drug use in drug legislation which causes injustice for individuals who have not consumed but are subject to articles with heavier penalties. The implementation of the drug criminal law policy still faces ambiguity in distinguishing between addicts, abusers, and victims. This legal uncertainty often results in drug abusers being charged with articles that are heavier than dealers, thus causing injustice that worsens their condition and burdens correctional institutions. A fairer legal reconstruction is needed to clearly distinguish between users and dealers and prioritize rehabilitation rather than punishment for drug abusers themselves.